2023
DOI: 10.1002/adsc.202300035
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Deaminative Alkylation of Quinoxalin‐2(1H)‐ones via Electron Catalysis

Abstract: A visible‐light initiated deaminative C3 alkylation of quinoxalin‐2(1H)‐ones with Katritzky salts is reported. This radical process provides an approach to a range of C3 alkylated quinoxalin‐2(1H)‐one derivatives in 40–96% yields under metal‐ and external photocatalyst‐free conditions. The reaction is enabled by the deprotonation of acidic aminyl radical intermediates to generate the corresponding radical anions, which act as single electron transfer reducing reagents to sustain the radical chain. The late‐sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…Control experiments showed that the reaction did not proceed in the absence of light, demonstrating that the purple LEDs were essential (entry 9). Contrary to the known 3-alkylquinoxalin-2(1H)-one syntheses, [27] the yield of our reaction under argon was almost identical to that under air (entry 10), proving that the reaction was not sensitive to oxygen.…”
Section: Resultscontrasting
confidence: 58%
See 3 more Smart Citations
“…Control experiments showed that the reaction did not proceed in the absence of light, demonstrating that the purple LEDs were essential (entry 9). Contrary to the known 3-alkylquinoxalin-2(1H)-one syntheses, [27] the yield of our reaction under argon was almost identical to that under air (entry 10), proving that the reaction was not sensitive to oxygen.…”
Section: Resultscontrasting
confidence: 58%
“…On the basis of the above-described experimental results and reported literature, [27] we propose that photoinduced CÀ H alkylation reactions between quinoxalin-2(1H)-ones and Katritzky salts proceed via EDA complexes by means of the mechanism illustrated in Scheme 4. First, an EDA complex is generated between the pyridinium salt and the NaOAc.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations